ANALISIS PENGARUH KUALITAS SISTEM MANAJEMEN TERHADAP KINERJA RANTAI PASOK KASUR VELBOA DI UD RAJA KARPET - M. Bagus Alamsyah; Achmad Misbah; Mas'ud, M. Imron (Journal Knowledge Industrial Engineering (JKIE), 2020)
Small industry has a significant role in supporting the peopleâ€™s economy even during the crisis that hit indonesia in mid-1997. Many small industries were able to survive this crisis situation. Small industry is able to survive because small industry is very flexible and responds very quickly to changes, besides that most of the raw materials and natural resources used are local. This study aims to analyze the effect of quality management systems on supply chain performance using the â€œTriple Aâ€ method in improving the supply chain performance of production management systems an delivery of velboa mattresses in UD RAJA CARPET and the number of samples used in this study were 30 respondents. In supply chain management, there is a theory of â€œTriplle Aâ€ suplly chain namely yaitu agile, adaptability , alignment. Agile a positive and significant effect on supply chain performance variables, adaptability has no positive an insignificant effect on supply chain performance variables, aligment has a positive and significant effect on supply chain performance variables. The conclusions that can be taken in this study regarding the quality analysis of the velboa mattress management system in UD king carpet on the performance of the â€œTriplle Aâ€ suplly chain strategy in improving the performance of the velboa matterss production and delivery supply chain are as follows: variable â€œTriplle Aâ€ has a positive and insignificant effect in improving quality performance. Suplly chain management system production and delivery of velboa mattress in UD king carpet, these results support the hypothesis proposed, as evidenced by the F test obtained F count of 0,351 and a significant value of 0,789 < 0,05 N=30 of 0,361.